PENGARUH PENGGUNAAN E-TAX DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK RESTORAN DI KOTA PALEMBANG ( Studi Kasus Pada Badan Pengelola Pajak Daerah Kota Palembang ) - Putri, Jauliyan Ayunda; Kurniawan, M Orba; Welly, Welly; Milzan, Milzan; Sabrina, Nina (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
This research aims to determine the partial effect of using E-Tax and Taxpayer Awareness on Taxpayer Compliance in Palembang City Restaurants. The type of research used is associative. The population of this study was 432 respondents, the sample selected was 100 restaurants with a sampling technique using cluster random sampling. The data used in the research is primary data. The t test results show that the variable E-Tax Use has an effect on restaurant taxpayer compliance, while the Taxpayer Awareness variable has no effect on restaurant taxpayer compliance. The results of the coefficient of determination with an error rate of 10% show that the variables of e-tax use and taxpayer awareness and restaurant Taxpayer Compliance are 44.5%